2023
DOI: 10.3390/brainsci13040688
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Depression in the Post-COVID-19 Syndrome: Correlation between Excitatory Symptoms in Depression and Physical Burden after COVID-19

Abstract: The relationship between depression and post-COVID-19 disease syndrome (post-COVID-19 syndrome) is established. Nevertheless, few studies have investigated the association between post-COVID-19 syndrome and mixed depression, i.e., a specific sub-form of depression characterized by high level of excitatory symptoms. Aims of the present study are: (a) to compare the post-COVID-19 syndrome’s burden in depressed and non-depressed patients, and (b) to investigate the correlation between post-COVID-19 syndrome’s bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Despite multiple reports on cognitive and depressive impairments [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 43 ] persisting for a year or longer after COVID-19 recovery [ 8 , 44 , 45 ], no studies have shown cognitive impairment in patients with clinically diagnosed post-COVID depression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite multiple reports on cognitive and depressive impairments [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 43 ] persisting for a year or longer after COVID-19 recovery [ 8 , 44 , 45 ], no studies have shown cognitive impairment in patients with clinically diagnosed post-COVID depression.…”
Section: Discussionmentioning
confidence: 99%
“…Simonetti et al [ 5 ] found an association between post-COVID-19 syndrome and mixed depression, i.e., a specific sub-form of depression characterized by a high level of excitatory symptoms. The group of depressed patients was formed only on the basis of the Hamilton scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some publications described differences in symptoms of PCD and MDD. Simonetti et al [17] found high level of excitatory symptoms in post-COVID-19 syndrome, which is more likely corresponded to a mixed form of depression. In contrast, the comparative analysis of biomarkers suggested a similar etiopathogenesis and inflammatory hypothesis for post-COVID depression and MDD [18].…”
mentioning
confidence: 96%